2008
DOI: 10.1097/gim.0b013e3181833793
|View full text |Cite
|
Sign up to set email alerts
|

Candidate gene/loci studies in cleft lip/palate and dental anomalies finds novel susceptibility genes for clefts

Abstract: Purpose: We revisited 42 families with two or more cleft-affected siblings who participated in previous studies.Complete dental information was collected to test the hypothesis that dental anomalies are part of the cleft phenotype spectrum, and can provide new opportunities for identification of cleft susceptibility genes. Methods:Genotypes from 1489 single nucleotide polymorphism markers located in 150 candidate genes/loci were reanalyzed. Two sets of association analyses were carried out. First, we ran the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
69
1
5

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(76 citation statements)
references
References 50 publications
1
69
1
5
Order By: Relevance
“…A genome-wide linkage study of families with clefting suggested genetic differences between those with and without dental anomalies (Vieira et al 2008b). Also, previous associations between cleft candidate genes/loci, including MSX1, PAX9, IRF6, ANKS6, ERBB2, ABAC4-ARHGAP29, 8q24, and 6q14, and specific patterns of dental anomalies in individuals with clefts (Vieira et al 2004;Modesto et al 2006;Vieira et al 2008a;Letra et al 2012;Yildirim et al 2012) support the hypothesis of a common genetic link between oral clefts and dental anomalies. However, they may also be partly explained by mechanical effects of the cleft and surgery if these variants affect cleft type and severity.…”
mentioning
confidence: 71%
“…A genome-wide linkage study of families with clefting suggested genetic differences between those with and without dental anomalies (Vieira et al 2008b). Also, previous associations between cleft candidate genes/loci, including MSX1, PAX9, IRF6, ANKS6, ERBB2, ABAC4-ARHGAP29, 8q24, and 6q14, and specific patterns of dental anomalies in individuals with clefts (Vieira et al 2004;Modesto et al 2006;Vieira et al 2008a;Letra et al 2012;Yildirim et al 2012) support the hypothesis of a common genetic link between oral clefts and dental anomalies. However, they may also be partly explained by mechanical effects of the cleft and surgery if these variants affect cleft type and severity.…”
mentioning
confidence: 71%
“…These results have been observed in other epidemiological studies focused on cleft lip and/or palate (21) and confirmed the strong influence of genetic background. Nevertheless, the statistical relationship between (17)(18)(19)(20). Therefore, the next step in our research program will be to ascertain specific genetic alterations that are intrinsically linked to cleft lip and/or palate in this Mexican population.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies and reviews (17)(18)(19)(20) identified genes that may play an important role in the etiology of cleft lip and/or palate, directly or through modifying the effect of environmental agents. Although several socio-demographic characteristics already have been identified as risk factors--such as father's and mother's age, sex, or even marital status (11,21,22), little information exists about the role of socioeconomic status (23)(24)(25).…”
mentioning
confidence: 99%
“…Thus the data suggest that the WNT signalling pathway may contribute to as much as 3-5% of NS CLP and will be a consideration in the clinical management of CL/P [24].…”
Section: Discussionmentioning
confidence: 99%